Keys to linking GCMC simulations and shale gas adsorption experiments - Chen, G.; Lu, S.; Zhang, J.; Xue, Q.; Han, T.; Xue, H.; Tian, S.; Li, J.; Xu, C.; Pervukhina, Marina (Elsevier Ltd, 2017)
A good consistence between the grand canonical Monte Carlo (GCMC) simulation results and the adsorption experimental measurements is an important precondition to reveal the shale gas adsorption mechanisms by the GCMC method. To better link the simulations and the experiments, we investigated the expression of the excess adsorption amount and the reasonability of selecting the critical parameters by performing the GCMC simulations of CH4 in the Na-Montmorillonite simulation cell with the pore size of 4 nm at the temperature of 90 °C under varying pressures. It is found that the excess adsorption amount in the nanopore in the simulations and between the simulations and the experiments are comparable by expressing it in per unit surface area of the adsorbent. The accessible volume probed by the corresponding gas molecule is the theoretical value of the free volume, and the determination of the bulk gas density from the GCMC method, which keeps the same method with the calculation of the absolute loading number of gas molecules, will eliminate the system error. We expect the findings are useful in the further investigation on the shale gas adsorption mechanisms by combing the GCMC simulations and the adsorption experiments.